Analisis Kinerja Keuangan PT. Bank Mandiri (Persero) Tbk Menggunakan Rasio Likuiditas Dan Rasio Profitabilitas Periode 2019-2023 - Lutfia Nurbi Syahda; Ferdina Watiningsih (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to assess the ability of banks to maintain liquidity and profitability amid economic changes. The method used is a quantitative descriptive approach through the analysis of liquidity ratios (current ratio, quick ratio, and cash ratio) and profitability ratios (return on assets, return on equity, and net profit margin). The results show that Bank Mandiri’s liquidity ratios are relatively stable, although the average Current Ratio of 123.6% is slightly below Bank Indonesia’s industry standard of 125%, while the Quick Ratio and Cash Ratio indicate better performance. In terms of profitability, Bank Mandiri demonstrates very strong performance, as reflected by the increase in Return on Assets from 2.58% in 2019 to 3.43% in 2023, as well as a Return on Equity reaching 20.88% in 2023. The average Net Profit Margin of 32.22% also indicates the bank’s ability to generate profits optimally. Keywords: Financial Performance, Liquidity Ratios, Profitability Ratios, PT Bank Mandiri (Persero) Tbk.